KECEMASAN MATEMATIK DAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMA - Wahyu Hidayat; Delifya Bunga Ayudia (Universitas Muhammadiyah Prof Dr HAMKA, 2019)
This research aims to analyze and examine deeply about the students' mathematical anxiety and mathematical problem-solving of high school students. The  research method used the correlational. The population in this research are high school students in West Bandung. Meanwhile, the sample of this research is 27 people that are purposively assigned to one of high schools in Cihampelas. Instruments used in this research are tests and non-tests. The results of this research shows that the abilities of mathematical problem solving of high school students are negatively affected by 57.1% of mathematical anxiety while 42.9 % is influenced by other factors beyond students' mathematical anxiety.